1992
DOI: 10.1007/bf01705041
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of central venous oxygen saturation versus mixed venous oxygen saturation in critically ill patients

Abstract: Continuous monitoring of mixed venous (SvO2) and central venous (ScO2) oxygen saturation was compared in 7 critically-ill patients (Apache II score: 19 +/- 2.1) to determine whether or not information derived from ScO2 were reliable in clinical practice. Patients were catheterized with both a pulmonary artery (PA) and a central venous (CV) catheter, each of them mounted with fiberoptic sensors (Opticath PA Catheter P7110 and Opticath CV Catheter U440, Abbott). A total of 580 comparative measurements were obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(17 citation statements)
references
References 18 publications
3
14
0
Order By: Relevance
“…On the basis of the present study, the net effect of these factors seems unpredictable. Our results seem concordant with earlier findings [6,8,16]. The first study described a small heterogeneous group of patients with septic shock.…”
Section: Discussionsupporting
confidence: 93%
“…On the basis of the present study, the net effect of these factors seems unpredictable. Our results seem concordant with earlier findings [6,8,16]. The first study described a small heterogeneous group of patients with septic shock.…”
Section: Discussionsupporting
confidence: 93%
“…These results are supported by Lee et al [16], who found a good correlation in normal subjects (r = 0.88) but not in patients in shock (r = 0.73). Martin et al [17]studied 7 critically ill patients with 448 consecutive measurements of the two parameters and found that there is a poor correlation between them during periods with or without medical intervention (r = 0.48 and 0.62, respectively) and they concluded that the two parameters are not interchangeable. They also found that the difference between the two parameters was >5% in 50% of the measurement, that abrupt changes in SvO 2 were not detected by ScvO 2 in 18% of the measurements and that there is poor correlation between changes in the two parameters during periods without (r = 0.70) and with therapeutic interventions (r = 0.77).…”
Section: Discussionmentioning
confidence: 99%
“…However, he found a substantial improvement in correlation (r = 0.94) when he compared oxygen content to oxygen saturation (by multiplication of saturation by a common hemoglobin value) and he concluded that the results are mathematically coupled to a degree that precludes final conclusions and thus necessitates further prospective evaluation. Finally, Vincent [19], using the data of Martin et al [17]concluded that ScvO 2 should not be considered as a reliable substitute for SvO 2 . However, the very small number of patients of this study and thus the dependent nature of the measurements make these results inaccurate for final results and conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Central venous oxygen saturation (ScvO 2 ) can be measured from a venous blood gas drawn from any central venous catheter (preferably in the upper extremities), so it is often used as a practical substitute. Multiple studies have questioned the reliability of ScvO 2 to predict SvO 2 (even allowing for + 10% error) (1821). ScvO 2 is generally regarded as not necessarily equivalent to SvO 2 but potentially useful for trending changes with therapy.…”
Section: Monitoringmentioning
confidence: 99%